2019
DOI: 10.1042/bsr20190610
|View full text |Cite
|
Sign up to set email alerts
|

Qingyihuaji formula reverses gemcitabine resistant human pancreatic cancer through regulate lncRNA AB209630/miR-373/EphB2-NANOG signals

Abstract: To investigate the possible mechanism of Qingyihuaji formula (QYHJ) for reversing gemcitabine (GEM) resistant human pancreatic cancer. Cell proliferation, apoptosis, migration and invasion were detected in CFPAC-1 cells. Xenograft mice established with CFPAC-1 through subcutaneous on 33 immunodeficient nude mice and randomly divided into four groups: vehicle, GEM (35 mg/kg), QYHJ (40 g/kg), and GEM + QYHJ (35 mg/kg + 40 g/kg) groups for 28-day treatment. Tumor growth and the mRNA expression of lncRNA AB209630,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Accumulating evidence suggested that TCM contributes to treating multifarious diseases, including malignancies [8,9]. The novel TCM formula Qingyihuaji (QYHJ) is produced by professor Luming Liu, which composed of Banzhilian (Herba Scutellariae Barbatae, HSB), Baihuasheshecao (HerbaHedyotdis, HBHY), Tiannanxing (Rhizoma Arisaematis erubescentis, RAE), Jiaogulan (Herba seu Radix Gynostemmatis pentaphylli, HSRGP), and Doukou (Fructus Amomi Rotundus, FAR), which was widely used for the treatment of PC during the past decades [10][11][12]. Besides, our previous clinical studies suggested that QYHJ treatment combined with first-line clinical western medicine improves the survival of PC patients with liver metastases [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggested that TCM contributes to treating multifarious diseases, including malignancies [8,9]. The novel TCM formula Qingyihuaji (QYHJ) is produced by professor Luming Liu, which composed of Banzhilian (Herba Scutellariae Barbatae, HSB), Baihuasheshecao (HerbaHedyotdis, HBHY), Tiannanxing (Rhizoma Arisaematis erubescentis, RAE), Jiaogulan (Herba seu Radix Gynostemmatis pentaphylli, HSRGP), and Doukou (Fructus Amomi Rotundus, FAR), which was widely used for the treatment of PC during the past decades [10][11][12]. Besides, our previous clinical studies suggested that QYHJ treatment combined with first-line clinical western medicine improves the survival of PC patients with liver metastases [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of some TCM extracts and gemcitabine are also reported to have better antitumor effects in pancreatic cancer therapy than gemcitabine alone. Oridonin was shown to overcome gemcitabine resistance in PANC-1/Gem cells (24), and melittin, Qingyihuaji formula (QYHJ) and curcumin have been demonstrated to promote gemcitabine sensitivity in human pancreatic cancer treatment (25)(26)(27). However, to the best of our knowledge, the anticancer effect of the combination of Huaier and gemcitabine has not been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, studies on hepatocellular carcinoma and on pancreatic ductal adenocarcinoma showed AB209630 down-regulation in tumor samples compared to adjacent tissue ( 46 , 47 ). Published data indicate a possible correlation between the expression of NANOG and AB209630 in human pancreatic cancer cells ( 21 ). To the best of our knowledge, this is the first study on the expression of AB209630 in OSCC carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Certain lncRNAs have already been shown that have potential to influence stemness-associated transcription factors, including NANOG ( 22 ). Based on the literature search, we selected RoR, SNHG1 and AB209630 , which were experimentally validated that either sponge miR-145 and miR-34a or directly or indirectly influence NANOG expression ( 19 21 ). Additionally, we analyzed the expression level of TP53 since it is a connection point in the regulation of selected ncRNAs ( 23 25 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation